Connecting Continents Archaeology and History in the Indian Ocean World - Seetah, Krish (Ohio University Press, 2018)
In recent decades, the vast and culturally diverse Indian Ocean region has increasingly attracted the attention of anthropologists, historians, political scientists, sociologists, and other researchers. Largely missing from this growing body of scholarship, however, are significant contributions by archaeologists and consciously interdisciplinary approaches to studying the region's past and present.Connecting Continents addresses two important issues: how best to promote collaborative research on the Indian Ocean world, and how to shape the research agenda for a region that has only recently begun to attract serious interest from historical archaeologists. The archaeologists, historians, and other scholars who have contributed to this volume tackle important topics such as the nature and dynamics of migration, colonization, and cultural syncretism that are central to understanding the human experience in the Indian Ocean basin.This groundbreaking work also deepens our understanding of topics of increasing scholarly and popular interest, such as the ways in which people construct and understand their heritage and can make use of exciting new technologies like DNA and environmental analysis. Because it adopts such an explicitly comparative approach to the Indian Ocean, Connecting Continents provides a compelling model for multidisciplinary approaches to studying other parts of the globe.Contributors: Richard B. Allen, Edward A. Alpers, Atholl Anderson, Nicole Boivin, Diego Calaon, Aaron Camens, Saša Čaval, Geoffrey Clark, Alison Crowther, Corinne Forest, Simon Haberle, Diana Heise, Mark Horton, Paul Lane, Martin Mhando, and Alistair Patterson.